Perceptions on the risk communication strategy during the 2013 avian influenza A/H7N9 outbreak in humans in China: a focus group study - Richun Li; Ruiqian Xie; Chong Yang; Melinda Frost (World Health Organization Regional Office for the Western Pacific, 2016)
Objective: To identify the general public's perceptions of the overall risk communication strategy carried out by Chinese public health agencies during the first wave of avian influenza A(H7N9) outbreak in humans in 2013. Methods: Participants were recruited from communities in Beijing, Lanzhou and Hangzhou, China in May and June 2013 by convenience sampling. Demographics and other relevant information were collected using a self-administered questionnaire. Focus group interviews were conducted using a set of nine pre-developed questions and a tested moderator guide. The interviews were audio recorded and were transcribed verbatim. The constant comparative method was used to identify trends and themes. Results: A total of nine focus group interviews, with 94 participants recruited from nine communities, were conducted. Most participants received H7N9 information via television and the Internet. A majority of the participants appreciated the transparency and timeliness of the information released by the government. They expressed a sense of trust in the recommended public health advice and followed most of them. The participants suggested that the government release more information about clinical treatment outcomes, have more specific health recommendations that are practical to their settings and expand the use of new media channels for risk communication. Conclusion: The public perceived the overall risk communication strategy by the Chinese public health agencies as effective, though the moderator had a governmental agency title that might have biased the results. There is a need to expand the use of social media for risk communication in the future.